Faktor yang Mempengaruhi Kekurangan Energi Kronis (KEK) pada Ibu Hamil di Puskesmas Cinta Karya Kecamatan Plakat Tinggi Kabupaten Musi Banyuasin Tahun 2025 - Ikrimah Juniarti; Intan Kumalasari; Maliha Amin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a long-term nutritional disorder caused by inadequate energy and protein intake, which may endanger the health of both mother and fetus. CED in pregnant women is indicated by an Upper Arm Circumference (LiLA) of less than 23.5 cm. The Cinta Karya Public Health Center has recorded a relatively high prevalence of CED compared to other health centers in Musi Banyuasin Regency. To determine the factors associated with the incidence of CED among pregnant women in the working area of Cinta Karya Public Health Center, Plakat Tinggi Sub-district, Musi Banyuasin Regency, in 2025. This was a quantitative study with a cross-sectional approach. A total of 82 pregnant women were selected using accidental sampling. Data were collected using questionnaires and direct LiLA measurements, then analyzed using the Chi-square test with a significance level of p<0.05. The prevalence of CED (LiLA < 23.5 cm) among pregnant women was 31.7%. Significant associations were found between CED and maternal age (p=0.003), pregnancy interval (p=0.002), family income (p=0.002), and knowledge level (p=0.002). The parity variable showed no significant relationship (p=0.399). Maternal age, pregnancy spacing, family income, and knowledge level significantly influence the incidence of CED in pregnant women. Nutritional education and proper pregnancy planning are essential in efforts to prevent CED.